2014
DOI: 10.1177/1088357614539837
|View full text |Cite
|
Sign up to set email alerts
|

Play Assessments and Developmental Skills in Young Children With Autism Spectrum Disorders

Abstract: Appropriate play behaviors facilitate language skills, increase cognitive skills, and provide opportunity for social interaction. However, play skills often present differently in children with Autism Spectrum Disorders (ASD). Currently, there are several global standardized ASD measures used during diagnostic evaluations that include, but are not limited to, assessment of play. However, it is unclear whether these measures examine similar aspects of play. This uncertainty is important to explore to better und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
0
22
0
4
Order By: Relevance
“…While other studies have compared ADOS composite scores to general play behaviors and developmental skills (e.g., Pierucci et al, 2015; Rodman et al, 2010), this study is the first that compares scores of Social Communication on the ADOS to peer communication in a structured, naturalistic setting. The activities and questions used to elicit behaviors that are scored on the ADOS Social Communication algorithm are able to be performed by a clinician in a short span of time in a clinical environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While other studies have compared ADOS composite scores to general play behaviors and developmental skills (e.g., Pierucci et al, 2015; Rodman et al, 2010), this study is the first that compares scores of Social Communication on the ADOS to peer communication in a structured, naturalistic setting. The activities and questions used to elicit behaviors that are scored on the ADOS Social Communication algorithm are able to be performed by a clinician in a short span of time in a clinical environment.…”
Section: Discussionmentioning
confidence: 99%
“…Pierucci and colleagues (2015) examined play in preschool-aged children by comparing clinician measures of play to parent reports of play and a measure of developmental skills. They compared a composite of the play scores from the ADOS (Module 1 and Toddler Module) and the Childhood Autism Rating Scales 2 nd Edition, Standard Form (CARS2-ST; Schopler, Van Bourgondien, Wellman, & Love, 2010) to play scores from the parent-reported Communication and Symbolic Behavior Scales Developmental Profile, Infant-Toddler Checklist (CSBS DP-ITC; Wetherby & Prizant, 2002) and Adaptive Behavior Assessment System, 2 nd Edition (ABAS-II; Harrison & Oakland, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the current study adds to the literature on early signs of autism in HR siblings by assessing delays or deficits in pretend play in both unstructured and structured contexts that are distinct from standard diagnostic assessments, while also rating social engagement with a play partner. Although limited pretend play is one diagnostic criterion for ASD, standard measures of pretending are only modestly correlated in preschool children with a diagnosis of ASD (Pierucci et al 2015). Therefore, this study of HR siblings at 22 months provides additional insight into characteristics of both play behavior and social interaction during play, associated with emerging ASD in toddlerhood.…”
Section: The Current Studymentioning
confidence: 99%
“…Consistent with previous research that has found better performance in heritage language intervention sessions (Lang et al, ), the present study found that bilingually exposed children with autism demonstrated more play behaviors in the presence of their heritage language. Because play is an important part of children's development (Pierucci, Barber, Gilpin, Crisler, & Klinger, ) and children with ASD often have impaired play skills (Baron‐Cohen, ; Jung & Sainato, ; Lang et al, ), this is not only an important but also a socially valid and relevant finding.…”
Section: Discussionmentioning
confidence: 99%